Cross-Cultural Marketing Strategy at The Koho Gili Air Hotel in Facing the Era of Globalization - Yolinda Islami; Lalu M. Furkan Islami (Journal of Accounting, Management, and Economic Development, 2026)
The rapid growth of international tourism in the Gili Islands triggered intense competition among local hospitality sectors, forcing businesses to adapt to diverse cultural backgrounds. However, many hotels still implemented generalized marketing standards that failed to resonate with the specific cultural expectations of global travelers. This study investigated how cultural differences affected international guest satisfaction and operational alignment. The primary objective of this research was to formulate an effective cross-cultural marketing strategy for The Koho Gili Air Hotel using Hofstede’s six cultural dimensions framework. A qualitative descriptive approach was deployed to examine the phenomenon thoroughly. Primary data were gathered through semi-structured interviews with hotel managers, front-line staff, and international and local guests at The Koho Gili Air. The collected operational data and interview transcripts were analyzed using interactive qualitative analysis, mapping the hospitality experiences against cultural metrics. The results indicated that significant cultural gaps existed in service expectations, particularly across the Power Distance and Indulgence versus Restraint dimensions. High power distance guests expected formal and highly respectful greeting procedures, whereas lower power distance guests preferred egalitarian and casual interactions. Furthermore, communication styles varied